2004
DOI: 10.1038/sj.gt.3302152
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of costimulation allows for repeated systemic administration of adenoviral vector in rhesus monkeys

Abstract: Immunogenicity of recombinant adenoviral (Ad) vectors severely hampers the clinical development of gene therapy protocols using repeated vector administrations. Inhibition of costimulation by APCs was explored as a strategy to circumvent the immune response against Ad particles. This strategy was tested in rhesus monkeys, treated transiently with chimeric anti-human CD40 and anti-human CD86 antagonist monoclonal antibodies (MAbs) at the time of systemic administration of a recombinant Ad vector. After Ad vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The striking inability of PG102-mediated CD40 engagement to trigger early signaling pathways in immune cells is consistent with its reported inhibition of CD40-mediated B cell effector functions (10,11). This also correlates with PG102-mediated inhibition of in vivo CD40-dependent promotion of inflammation and transplant rejection in animal models (12)(13)(14) and early clinical human studies (15). In some regards, this PG102-induced altered CD40 signaling resembles the "alternative" signaling pathways that bacterial superantigens are reported to trigger when they bind TCR/MHC complexes (reviewed in Ref.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The striking inability of PG102-mediated CD40 engagement to trigger early signaling pathways in immune cells is consistent with its reported inhibition of CD40-mediated B cell effector functions (10,11). This also correlates with PG102-mediated inhibition of in vivo CD40-dependent promotion of inflammation and transplant rejection in animal models (12)(13)(14) and early clinical human studies (15). In some regards, this PG102-induced altered CD40 signaling resembles the "alternative" signaling pathways that bacterial superantigens are reported to trigger when they bind TCR/MHC complexes (reviewed in Ref.…”
Section: Discussionsupporting
confidence: 81%
“…Subsequently, a chimeric form of 5D12 (ch5D12) containing human IgG4 constant regions was produced. The ch5D12 mAb prevents development of experimental autoimmune encephalomyelitis in marmosets (12), as well as prolongs the survival of kidney allografts and allows repeated systemic administration of adenoviral gene therapy vectors in rhesus monkeys (13,14). In an open-label dose-escalation phase I/IIa study of Crohn's disease patients, ch5D12 was well tolerated and showed promising clinical benefit (15).…”
mentioning
confidence: 99%
“…3D and Dataset S1, tab 13). Our results are compatible with the suggestion that Ad5 nAb may effectively lower the dose of the vaccine detected by the innate immune system (8,46) and are consistent with the reduced vaccine immunogenicity seen in vaccine recipients with nAb titers >200 (3). Our results are also compatible with a model in which nAbs negatively regulate innate signaling pathways.…”
Section: Discussionsupporting
confidence: 79%
“…The non-stimulatory antagonistic activity of Mab 5D12 (anti-human CD40) was demonstrated in various in vitro studies using different CD40-bearing cell types [20][21][22] and ch5D12 antagonist activity was validated in vivo using various non-human primate disease models. [23][24][25][26][27] Chimeric 5D12 (ch5D12) is a molecularly engineered human IgG 4 antibody containing the variable domains of the heavy and light chains of 5D12 and was constructed to reduce the potential for immunogenicity and to enhance the in vivo half-life of the 5D12 Mab when used in humans.…”
Section: Introductionmentioning
confidence: 99%